DESIGN OF MANAGEMENT INFORMATION SYSTEM OF FINAL ASSIGNMENT GUIDANCE (SIMBITA) WEB-BASED - eko Haryadi; Diah Wijayanti; Dewi Yuliandari; Syafrianto -; Asep Bambang (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
The implementation of guidance in two directions is carried out by discussing, conducting questions and answers, providing input and other activities. However, sometimes the guidance process carried out face-to-face experiences many obstacles so the coaching process does not run optimally and it is not as expected. The most common obstacle is when the supervisor is unable to attend the final assignment guidance. Communication barriers between students and supervisors also affect the success of the final assignment. Hence, it is necessary to develop a way to have the obstacles can overcome better. The method used to solve these problems using the system development life cycle method. The solution is currently using sms or online facilities such as email, social media, or the cloud from a third party. With this system, if face-to-face guidance activities are not possible, the process of preparing student final assignments can be carried out in order to be on time for the graduation of students in the institutions.